Plasma histamine and tumour necrosis factor-alpha levels in Crohn's disease and ulcerative colitis at various stages of disease - Hagel, Alexander; De Rossi, T.; Konturek, Peter; Albrecht, H.; Walker, Stefanie Elke; Hahn, Eckhart Georg; Raithel, M. (Journal of Physiology and Pharmacology, 2015)
Mast cells secrete numerous mediators and this study investigated plasma levels of histamine, and tumor necrosis factor alpha (TNF-?) in chronic inflammatory bowel disease (IBD). Plasma levels of histamine were determined in 68 patients with Crohn's disease (CD), 22 with ulcerative colitis (UC) and 13 controls. TNF-? levels were assessed in 29 CD patients, 11 UC patients, and in 11 controls. Plasma histamine levels in the control group were 0.25 ng (0.14 - 0.33) and showed no difference to CD (0.19 ng, 0.09 - 0.35) or UC (0.23 ng, 0.11 - 0.60). Significantly lower histamine levels were only found in CD patients on 5-aminosalicylic acid treatment (P <= 0.04). Plasma TNF-? levels in the control group were significantly lower 0.44 ml/m(2) (0 - 1.15) than in CD patients (4.62 ml/m(2), 1.82 - 9.22, P = 0.005) or UC (3.14 ml/m(2); 0.08 - 11.34, P = 0.01). In CD disease activity, fistula, and extraintestinal manifestations (EM) were associated with significantly higher plasma TNF-? values, but not the type of treatment. We concluded that in contrast to TNF-?, histamine levels were normal in CD and UC. There is no correlation with histamine and thus the proportion of TNF-? secreted from mast cells in the plasma in patients with IBD is less important.
EVALuna2:2032